DDVV Inequality on Submanifolds Coupled with a Slant Factor in Quaternionic Kaehler Manifolds - Rawan Bossly; Majid Ali Choudhary; Mohd Danish Siddiqi; Oḡuzhan Bahadır; Mehmet Gülbahar (Axioms)
This work aims to provide generalized Wintgen inequalities for slant submanifolds embedded in quaternionic space forms, taking into consideration both semi-symmetric metric and semi-symmetric non-metric connections. Moreover, we discuss the same inequality for totally real, anti-invariant, and invariant submanifolds on quaternionic space forms, endowed with both semi-symmetric metric and semi-symmetric non-metric connections. We also characterized the equality case through specific forms of shape operators of Wintgen inequalities for these classes of submanifolds in quaternionic space forms, admitting a semi-symmetric metric connection and a semi-symmetric non-metric connection.